Control of photoinduced charge transfer through selective cyanation of spirofluorene-bridged N-heterotriangulenes - Jocic, Angelina; Galindo, Danyellen; Weidlich, Anna; Zerhoch, Jonathan; Rominger, Frank; Buckup, Tiago; Deschler, Felix; Dreuw, Andreas; Kivala, Milan (Advanced optical materials, 2024)
A series of selectively cyanated spirofluorene-bridged N-heterotriangulenes (N-HTAs) with three to nine cyano groups are synthesized via a newly developed synthetic strategy. X-ray crystallographic analysis of the compounds revealed a tripod-like molecular shape with the fluorenyl moieties arranged in a perpendicular fashion around the nitrogen-centered N-HTA core. The solid state packing is found to be strongly influenced by the dipolar cyano functions. Under electrochemical conditions, the N-HTA core is prone to undergo a reversible one-electron oxidation toward the nitrogen-centered radical cation, which becomes increasingly difficult as the number of the cyano acceptors, and consequently the ionization potential, increases. While a clear bathochromic shift is observed in the steady-state UV-vis absorption spectra, the fluorescence behavior is complex and strongly dependent on the position and number of the cyano groups. The compound with six cyano functions at the fluorenyl flanks is unique within the series and shows a broad emission maximum at 499 nm and an unusually large Stokes shift of 10 171 cm−1. Time-resolved absorption and fluorescence measurements, supported by quantum chemical calculations, identified this spectroscopic signature to originate from fast and robust photoinduced intramolecular charge transfer.